STUDY OF AMINO ACID COMPOSITION OF RABBIT MEAT (Scientific journal of the Fergana State University, 2025)
In this article presents, the results of the research of the amino acid content of rabbit meat grown in Fergana region by the method of high-performance liquid chromatography. According to the results of the analysis, the amount of 20 amino acids involved in protein synthesis was determined in pork meat. The highest amount of leucine was detected and its amount was equal to 9.015 mg/g (10.95%). The amount of leucine is 1.29-43.36 times more than other amino acids. Exchangeable amino acids accounted for 42.3% of the total amount of amino acids. Among exchangeable amino acids, arginine, glutamic acid, proline and cysteine ​​have a relatively large amount. Non-exchangeable amino acids made up 57.7% of the total amount of amino acids. Among non-exchangeable amino acids, amino acids such as leucine, histidine, valine, lysine, phenylalanine, tryptophan and isoleucine have a relatively large amount. According to the research results, it can be noted that rabbit meat is rich in non-exchangeable amino acids.